Do the Best Go West? An Analysis of the Self-Selection of Employed East-West Migrants in Germany - Herbert Brücker; Parvati Trübswetter (Institute for the Study of Labor (IZA), 2004)
Since the inequality of earnings in East Germany has approached West German levels in the late 1990s, the standard Roy model predicts that a positive selection bias of East-West migrants should disappear. Using a switching regression model and data from the IABemployment sample, we find however that employed East-West migrants remain positively self-selected with respect to unobserved abilities. This result is consistent with the predictions of our extended Roy model which considers moving costs that are negatively correlated with labour market abilities of individuals. Moreover, we find that wage differentials as well as differences in employment opportunities are the central forces which drive East-West migration after unification.
Keywords: P23; J61; R23; 330; migration; self-selection; East Germany; Binnenwanderung; Regionale Arbeitsmobilität; Migrationstheorie; Brain Drain; Schätzung; Neue Bundesländer; Alte Bundesländer; Selbstselektion